Influence of protease inhibitors on the degradation of sound, sclerotic and caries-affected demineralized dentin - Oliveira-Reis, B. [UNESP]; Maluly-Proni, A. T. [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Vasconcelos, G.; Bresciani, E. [UNESP]; Prakki, A.; Santos, Paulo Henrique dos [UNESP] (Elsevier, 2019)
The aim of this study was to evaluate influence of protease inhibitors on degradation of sound, sclerotic and caries-affected dentin. Thirty-nine molars were used, thirteen for each dentin condition. Three slices were obtained from each tooth, each one immersed in the following different solutions for 1 h: 1)artificial saliva; 2)2% chlorhexidine; 3)0.5% epigallocatechin-gallate (EGCG). After immersion, samples were subjected to enzymatic degradation challenge (collagenase from Clostridium histolyticum). Nanohardness (HIT)and elastic modulus (Er)were measured before and after enzymatic challenge, as well as the ultimate tensile strength (UTS). Results of UTS, HIT and Er tests were submitted to repeated measurements ANOVA and Tukey post-test (α = 0.05). Higher values of UTS were found for sound dentin in control (40.30 ± 21.38 MPa)and 0.5% EGCG (30.05 ± 19.67 MPa)groups. Before degradation, higher values of HIT (0.237 ± 0.062 GPa)and Er (5.58 ± 1.75 GPa)were found for 0.5% EGCG group in caries-affected dentin. After degradation, 2% chlorhexidine group had higher values of HIT and Er for sound (0.134 ± 0.020 GPa and 3.57 ± 0.40 GPa)and sclerotic (0.201 ± 0.048 GPa and 4.30 ± 0.56 GPa)dentin. The 2% chlorhexidine showed best effect increasing HIT and Er, mainly for sclerotic dentin, before/after enzymatic degradation. The 0.5% EGCG showed better effect on HIT and Er in caries-affected dentin, before enzymatic degradation.
Keywords: Camellia sinensis; Catechin; Collagen; Dentin